Hydrogen bond and surface stress relaxation by aldehydic and formic acidic molecular solvation - Chen, Jiasheng (2019)
Solvation of aldehydes and formic acids has an important impact to health care because these additives can damage DNA and denature proteins causing cancers with the mechanism behind remaining great challenge. From the perspective of solvent hydrogen bond (O:HO or HB with “:” being the electron lone pair of oxygen) transition from the mode of the ordinary water to the hydrating states, we examined the solvation bonding dynamics and the solute capabilities of O:HO bond and surface stress transition using differential Raman spectroscopy and contact angle detection. Results suggest that besides the short-range O:H van der Waals (vdW) bond, the H ↔ H and O: ⇔ :O repulsive intermolecular interactions, and the molecular dipolar polarization play important roles in disrupting the solution network and surface stress. Observations may infer the manner of DNA fragmentation by aldehyde and formic acid disruption.